ANALYSIS OF TEMPO AND KOMPAS ONLINE MEDIA FRAMING TOWARDS REPORTING THE ISSUES OF THE 2024 PRESIDENTIAL ELECTION POSTPONEMENT - Effendy, Yusuf Septian Nur (UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
Abstract: The purpose of this study is to find out how one of the reports made by the online media Tempo and Kompas in framing news about the postponement of the 2024 election through the framing analysis approach of the Zhongdang Pan and Gerald M. Kosicki model. The method used is descriptive-interpretative research. Researchers interpret news about the issue of delaying the 2024 presidential election by taking news samples from the online media Tempo and Kompas which were published on April 10 and 12, 2022. The results of this study are 1) News carried out by Tempo tend to be neutral and as it is, in contrast to Kompas which include opinions from political communication experts 2) both news stories have used inverted pyramid systematics. It can be seen from the leads in both news. The difference is that Tempo media reports tend to be short but dense, while Kompas is quite long because it adds news content by including opinions from political communication experts.